Occlusal scheme effect on the biomechanical response of full-arch dental prosthesis supported by titanium implants: A systematic review - Gomes, Laís Carolina Landim [UNESP] (2021)
Dental implant-supported prosthesis are widely used in oral reconstruction of totally edentulous patients. Nonetheless, one of the most common failures in these cases is caused by overloading from improper occlusion. The aim of this work was to determine if the occlusal scheme influences the biomechanical response in implant-supported dental prostheses. Searches were conduct is several databases (PubMed/MEDLINE, The Cochrane Library, Web of Science, Scopus, LILACS, and Opengrey). We found 632 publications and 521 studies remained after removing duplicates. After applying the inclusion criteria, five studies were used in this systematic review: one clinical trial, one retrospective clinical trial, one in vitro and two in silico. The results show the lack of clinical and laboratory studies about occlusion in implant-supported prostheses. Although there are several studies regarding implant occlusion schemes, there remains a lack of scientific evidence to support that one specific occlusal scheme is superior to another, or to help define the ideal occlusal scheme that improves the clinical outcome. It can be concluded, however, that the proper distribution of loads and the absence of occlusal interferences can increase implant longevity. Thus, more clinical and laboratory studies must be carried out to obtain an occlusal scheme that favors the clinical success of implant rehabilitation.